2006
DOI: 10.2527/2006.8461454x
|View full text |Cite
|
Sign up to set email alerts
|

Growth and body composition of dairy calves fed milk replacers containing different amounts of protein at two feeding rates1

Abstract: Previous research has demonstrated that increasing the CP concentration from 16 to 26% in milk replacers fed to male preruminant dairy calves at 1.5% of BW (DM basis) daily resulted in increased ADG, G:F, and deposition of lean tissue. However, the effects of dietary CP would be expected to vary depending on ME intake. Here, male Holstein calves < 1 wk old were used to determine the effects of feeding rate and CP concentration of isocaloric, whey protein-based milk replacers on growth and body composition. Aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

38
185
12
11

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(246 citation statements)
references
References 23 publications
38
185
12
11
Order By: Relevance
“…The flowing agent was responsible for the small increase in average ash content in the current study compared with that reported in other studies (e.g. Bartlett et al, 2006). Drinking water was available at all times throughout the study.…”
Section: Animalssupporting
confidence: 45%
See 2 more Smart Citations
“…The flowing agent was responsible for the small increase in average ash content in the current study compared with that reported in other studies (e.g. Bartlett et al, 2006). Drinking water was available at all times throughout the study.…”
Section: Animalssupporting
confidence: 45%
“…Effects of milk replacer feeding regime Table 5 Summary of studies examining daily liveweight gains during the milk-feeding period Blome et al (2003) and Bartlett et al (2006) in which calves were offered MRs containing up to 260 g CP/kg DM. However, the response to increasing CP content does appear to decline when levels exceed approximately 220 g CP/kg DM as demonstrated by Donnelly and Hutton (1976) and Bartlett et al (2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted, however, that intake of Dried distillers grains in lactating beef cows maternal diets by calves during the neonatal treatment period in the current experiment was possible, and thus could have contributed to differences in BW. However, studies with milk replacer in dairy calves suggest that increasing protein increases calf BW and protein deposition, although protein may only be beneficial if energy supply is adequate (Bartlett et al, 2006). A portion of nitrogen requirements for nursing calves can be met by urea as early as 6 weeks of age (Brown et al, 1956), thus increased MUN in DDGS fed cows may have been responsible for increased growth rates of progeny.…”
Section: Milkmentioning
confidence: 99%
“…Several studies involving different FL have been conducted during the last decade in veal calves using the comparative slaughter technique (Gerrits et al, 1996;Diaz et al, 2001;Bartlett et al, 2006). Nevertheless, little attention has been paid to the dynamic change of the response of the calf over -E-mail: jean.noblet@rennes.inra.fr short periods of time.…”
Section: Introductionmentioning
confidence: 99%